The The Influence of Golden Triangle-Based Digital Learning Management on Learning at Islamic Senior High Schools in Bogor City - Syukri Indra; Ahmad Subagyo; Dyarini (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This study aims to test the significance of the golden triangle-based digital learning management (people, process, and technology) on learning at MAN (Islamic State Senior High School) in Bogor City. This study employed a quantitative method with SEM (Structural Equation Modeling) analysis. The research location was at State Islamic Senior High Schools (Madrasah Aliyah) in Bogor City, with a sample size of 126 respondents. Data collection used a questionnaire analyzed using SmartPLS software. The path analysis results yielded: X1 -> Y has a T-statistic of 3.084 > 1.96 and a P-value of 0.002 < 0.05; X2 -> Y has a T-statistic of 2.615 > 1.96 and a P-value of 0.009 < 0.05; X3 -> Y has a T-statistic of 4.270 > 1.96 and a P-value of 0.000 < 0.05. All three hypotheses tested partially in this study demonstrated significant correlations between variables. The calculation results obtained a significant R-square value of 0.617. This indicates that the exogenous variables in the model simultaneously explain 61.7% of the variance in the endogenous variables, while the remaining 38.3% is influenced by other factors not analyzed in this study. The implication of this research is that the implementation of digital learning management based on the golden triangle can be a strategic framework for improving the quality of learning in State Islamic Senior High Schools (Madrasah Aliyah) throughout Bogor City. Strengthening teacher competencies (people), management processes (process), and the availability of digital infrastructure (technology) has been proven to provide positive contributions. Madrasas can strengthen digital training programs for teachers and increase digital support facilities so that learning implementation can run more optimally and align with the needs of 21st-century education.